Engineers and auditors joint statement by the Institution of Civil Engineers and the Chartered Institute of Public Finance and Accountancy. (Thomas Telford, 1992)
This work aims to explain the relationship in the contract process between auditors and engineers without detracting from their independence. The possible confusion between the respective roles of auditors and engineers is born mainly out of inexperience and a mutual ignorance of each other's terms of reference.
Keywords: Construction industry -- Great Britain -- Auditing.; elektronické knihy; electronic books